2020
DOI: 10.3390/ma13225156
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-Rheological Fluid Assisted Abrasive Nanofinishing of β-Phase Ti-Nb-Ta-Zr Alloy: Parametric Appraisal and Corrosion Analysis

Abstract: The present work explores the potential of magneto-rheological fluid assisted abrasive finishing (MRF-AF) for obtaining precise surface topography of an in-house developed β-phase Ti-Nb-Ta-Zr (TNTZ) alloy for orthopedic applications. Investigations have been made to study the influence of the concentration of carbonyl iron particles (CIP), rotational speed (Nt), and working gap (Gp) in response to material removal (MR) and surface roughness (Ra) of the finished sample using a design of experimental technique. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…An evaluation of osseointegration using similar bone morphometrical parameters as in this study has been previously performed [ 49 ]. These results support those of material development of Ti alloys to which Zr, Nb, and Ta have been added [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…An evaluation of osseointegration using similar bone morphometrical parameters as in this study has been previously performed [ 49 ]. These results support those of material development of Ti alloys to which Zr, Nb, and Ta have been added [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Resultssupporting
confidence: 84%
“…The adverse effects of metal ions include the cytotoxicity of trace amounts of vanadium (V) and aluminum (Al) ions in Ti–6Al–4V alloy and the allergy-related characteristics of nickel (Ni) ions [ 2 , 3 , 4 ]. Recently, many types of Ti alloy containing noncytotoxic elements such as zirconium (Zr), niobium (Nb), tantalum (Ta), and molybdenum (Mo) have been developed for various medical applications [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Ti–15Zr–4Nb–(0 to 4) Ta alloy, which is an alpha (α)–beta (β)-type alloy, has been developed in Japan as a highly biocompatible alloy [ 17 ], and it is standardized in JIS T 7401-4 [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The casings of aluminum alloy electronic products are only 1–2 mm thick, requiring surface roughness to reach a few nanometers without any deformation, which traditional mechanical finishing methods find difficult to meet [ 10 , 11 ]. Magnetic field-assisted finishing has been proven to be a low-damage [ 12 , 13 , 14 , 15 ], ultra-precision grinding and polishing method [ 16 , 17 ] that can effectively perform planar finishing such as on glass [ 18 ], polymers [ 19 ], stainless steel [ 20 , 21 ], copper [ 22 , 23 ], and alloys [ 24 , 25 ]. Kataria et al developed a continuous flow magnetorheological fluid finishing process for the finishing of small holes of 6063 aluminum alloy, with a surface roughness from 7.3 µm to 10.5 nm [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results of the experimental studies confirmed that the effect of the curvature of the cut shape is important from the point of view of the efficiency of the glass-based brittle material-cutting process using AWJ. An interesting way of machining is described in [ 28 ], where Singh et al present the potential of magneto-rheological fluid-assisted abrasive finishing for generating precise surface topography of titan alloy for orthopedic applications. The corrosion performance of the finished samples has also been analyzed through simulated body fluid (SBF) testing.…”
mentioning
confidence: 99%